STRATEGI PENGEMBANGAN SUMBER DAYA MANUSIA DI PT. GAYA SUKSES MANDIRI KASEINDO ( SAFEWAY) SURABAYA - Susilowati, Sri; Farida, Ilya (Develop, 2019)
This research aims to know and understand strategy of human resource development at PT.  Gaya Sukses Mandiri Kaseindo (Safeway) Surabaya. The results of this research is a model of human resource development strategy that has been done by PT Gaya Sukses Mandiri Kaseindo (Safeway) Surabaya is as follows: 1.Selection of potential human resource. 2. Perform evaluation of human resource performance using KPI (Key Performance Indicator) 3. Giving an opportunity to employees to contribute ideas.  4. Appropriate career planning  5. Giving rewards and punishment 6. Conducting various Training and Human Resource Development :  Internal Training methode 1. 5C (Clear-out, Classify, Cleaning, Conformity, Custom) 2. Leadership Coaching Training and External Training methode : 1. Lean Management, 2. Negotiation Skill & Service Excellence Training. The company is responsible for improving work ability, the skills of its employees to be better. Human resource development strategy is a form of appreciation of a leader to employees in the form of humanis. Training and development is one solution to a number of problems decreasing the quality of the performance of organizations or institutions and agencies caused by decreased ability and obsolescence skills owned by employees. The purpose of training and development is to change attitudes, behavior, experience and performance of employee performance to be better.